High tunneling magnetoresistance induced by symmetry and quantum interference in magnetic molecular junctions. Issue 18 (13th April 2021) - Huang, Lin; Zeng, Yu-Jia; Wu, Dan; Luo, Nan-Nan; Feng, Ye-Xin; Fan, Zhi-Qiang; Tang, Li-Ming; Chen, Ke-Qiu
Abstract : A higher tunneling magnetoresistance ratio is obtained in the symmetric magnetic molecular junction due to the quantum interference, and it shows stronger ability to resist the influence of electron-vibration interaction and temperature. Abstract : Achieving high tunneling magnetoresistance (TMR) in molecular-scale junctions is attractive for their applications in spintronics. By using density-functional theory (DFT) in combination with the nonequilibrium Green's function (NEGF) method, we investigated the spin-resolved charge transport properties of molecular junctions based on Co-Salophene symmetric/asymmetric dimers. We found that nearly 100% spin-injection efficiency (SIE) can be achieved in parallel spin configuration with the spin dependent quantum interference effect. In particular, the high TMR is demonstrated to be closely related to the molecular symmetry, reaching 4600% and 2200% for a symmetric and asymmetric molecular junction (MJ), respectively. Further inelastic transport analyses reveal that the excellent TMR properties of the symmetric MJ can still be preserved in the electron-vibration interaction and temperature effects being considered, which provides an insight for designing future molecular integrated circuit devices.